On the wear comparative analysis of cutting tools made of composite materials based on polycrystalline cubic boron nitride when finish turning of AISI D2 (EN X153CrMoV12) steel - Ociepa Michał; Jenek Mariusz; Feldshtein Eugene (Сверхтвердые материалы, 2018)
This study presents the results of research on the condition of low content polycrystalline cubic boron nitride cutting tools (cBN-L) when finish turning of hardened AISI D2 tool steel. The least changes in the condition of wedges throughout the investigated turning feeds were observed for the composite cBN020 whereas the highest wear intensity was found for the composite cBN200. For all researched cutting materials, abrasive wear, as well intense adhesion were observed. У даному дослідженні представлено результати досліджень різального інструменту з полікристалічного кубічного нітриду бору (cBN-L) за умови низького вмісту кубічного нітриду бору при обробці загартованої інструментальної сталі AISI D2. Найменші зміни у стані клинів за досліджуваних подач при токарній обробці спостерігали для композиту cBN020, тоді як найвищу інтенсивність зносу виявлено для композиту cBN200. Для всіх досліджуваних різальних матеріалів спостерігали абразивний знос, а також інтенсивну адгезію. В этом исследовании представлены результаты исследований режущего инструмента из поликристаллического кубического нитрида бора (cBN-L) с низким содержанием кубического нитрида бора при обработке закаленной инструментальной стали AISI D2. Наименьшие изменения состояния клиньев при всех исследуемых подачах при токарной обработке наблюдали для композита cBN020, тогда как наибольшая интенсивность износа была обнаружена для композита cBN200. Для всех исследованных режущих материалов наблюдали абразивный износ, а также интенсивную адгезию.